The Influence of Coordination, Agility and Motivation Against Basketball Dribbling Skills in High School Extracurricular Participants - Ramadhan, Kevin; Asmawi, Mochamad; Rihatno, Taufik (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This study aims to determine information related to the influence of coordination, agility, and motivation on basketball dribbling skills in high school extracurricular participants. This thesis uses quantitative approach methods, survey methods and correlational techniques. The research for this thesis was conducted at SMA Islam Terpadu Raudhatul Jannah Kota Cilegon, Banten. The population in this study was 30 female basketball extracurricular participants. Based on the results of data analysis, description, examiner of research results, and discussion, conclusions can be drawn from this thesis research. Based on the t-test results of the first hypothesis, there is a direct effect of coordination on basketball dribbling skills by 44.1%. The results of the second hypothesis, that there is a direct influence of agility on basketball dribbling skills by 36.4%. The results of the third hypothesis, that there is a direct influence of motivation on basketball dribbling skills by 10.7%. The result of hypothesis four, there is a direct effect of coordination on motivation in extracurricular participants by 0.004%. The result of hypothesis five, there is a direct effect of agility on motivation in extracurricular participants by 87.2%. The results of hypothesis six, then the results of the motivation variable were not able to mediate the coordination variable on basketball dribbling skills and did not have a real mediating influence on the independent and bound variables. The results of hypothesis seven, then the results of the motivation variable were not able to mediate the agility variable on basketball dribbling skills and did not have a real mediating influence on the independent and bound variables. Thusly there is a direct influence on several variables studied so that there is a significant influence.